Unlocking Allelic Diversity for Sustainable Development of Salinity Stress Tolerance in Rice - Raghuvanshi, Rishiraj; Srivastava, Ashish K.; Verulkar, Satish; Suprasanna, Penna (Current Genomics, 2021)
Rice is a major cereal crop, negatively impacted by soil-salinity, both in terms of plant growth as well as productivity. Salinity tolerant rice varieties have been developed using conventional breeding approaches, however, there has been limited success which is primarily due to the complexity of the trait, low yield, variable salt stress response and availability of genetic resources. Furthermore, the narrow genetic base is a hindrance for further improvement of the rice varieties. Therefore, there is a greater need to screen available donor germplasm in rice for salinity tolerance related genes and traits. In this regard, genomics based techniques are useful for exploring new gene resources and QTLs. In rice, the vast allelic diversity existing in the wild and cultivated germplasm needs to be explored for improving salt tolerance. In the present review, we provide an overview of the allelic diversity in the Quantitative Trait Loci (QTLs) like Saltol, qGR6.2, qSE3 and RNC4 as well as genes like OsHKT1;1, SKC1 (OsHKT1;5/HKT8) and OsSTL1 (salt tolerance level 1 gene) related to salt tolerance in rice. We have also discussed approaches for developing salt-tolerant cultivars by utilizing the effective QTLs or genes/alleles in rice.
Keywords: OsHKT1; 5